Controlled-release hydromorphone and risk of infection in adults: a systematic review - Andrea C. Tricco; Amanda Parker; Areej Hezam; Vera Nincic; Fatemeh Yazdi; Yonda Lai; Charmalee Harris; Zachary Bouck; Ahmed M. Bayoumi; Sharon E. Straus (BMC, 2023)
Abstract Background Preliminary evidence suggests that people who inject drugs (PWID) may be at an increased risk of developing infective endocarditis (IE), hepatitis C virus (HCV) infection, and/or human immunodeficiency virus (HIV) infection from hydromorphone controlled-release formulation. The hypothesized mechanism is related to insolubility of the drug, which promotes reuse, leading to contamination of injecting equipment. However, this relationship has not been confirmed. We aimed to conduct a systematic review including adult PWID exposed to controlled-release hydromorphone and the risk of acquiring IE, HCV, and HIV. Methods We searched MEDLINE, EMBASE, and Evidence Based Medicine reviews from inception until September 2021. Following pilot testing, two reviewers conducted all screening of citations and full-text articles, as well as abstracted data, and appraised risk of bias using the Newcastle-Ottawa scale and Effective Practice and Organization of Care tool. Equity issues were examined using the PROGRESS-PLUS framework. Discrepancies were resolved consistently by a third reviewer. Meta-analysis was not feasible due to heterogeneity across the studies. Results After screening 3,231 citations from electronic databases, 722 citations from unpublished sources/reference scanning, and 626 full-text articles, five studies were included. Five were cohort studies, and one was a case-control study. The risk of bias varied across the studies. Two studies reported on gender, as well as other PROGRESS-PLUS criteria (race, housing, and employment). Three studies focused specifically on the controlled-release formulation of hydromorphone, whereas two studies focused on all formulations of hydromorphone. One retrospective cohort study found an association between controlled-release hydromorphone and IE, whereas a case-control study found no evidence of an association. One retrospective cohort study found an association between the number of hydromorphone controlled-release prescriptions and prevalence of HCV. None of the studies specifically reported on associations with HIV. Discussion Very few studies have examined the risk of IE, HCV, and HIV infection after exposure to controlled-release hydromorphone. Very low-quality and scant evidence suggests uncertainty around the risks of blood-borne infections, such as HCV and IE to PWID using this medication.